Effect of exposure to lead on postural control in workers. Issue 3 (1st March 2000) - Ratzon, N; Froom, P; Leikin, E; Kristal-Boneh, E; Ribak, J
Abstract : OBJECTIVES: To examine the effect of lead on postural control of workers who have been exposed to lead. METHODS: 63 Male, lead battery workers mean (SD) age 41.0 (7.4) were compared with 48 age matched male controls after excluding those with acute or chronic diseases. Exposed workers had mean (SD) past blood lead concentrations of 37.5 (9.2) μg/dl and 11.2 (5.7) years of employment. Postural control was measured with a computerised postural sway measurement system which measured both sway and total movements. RESULTS: Workers standing straight with eyes open on the bare plates had sway and total movements which were not notably different from controls. On the other hand increased movements were needed in the exposed workers to maintain stability (the general stability quotient 18.2 (5.4) v 15.4 (4.4) in controls, p<0.01) when standing directly on the footplates with closed eyes, , and with the head tilted (15.0 (3.8) v 11.5 (3.0) in controls, p<0.001). Exposed workers also had a trend for less ability to synchronise anterior posterior and lateral sway in the stress positions (0.0625) than had non-exposed workers . Significant but low correlations were found between the estimate of the chronic internal dose of lead and three of 10 of the postural control measurements, and present lead blood concentrations and only one of the 10 measurements and ( r values ranged from 0.21 to 0.31, p⩽0.03). CONCLUSIONS: These findings suggest that lead affects postural control in asymptomatic workers. Further studies are warranted to find whether workers with decreased postural control are at increased risk of accidents and the relation, if any, of these measurements with subsequent morbidity.